PARTISIPASI ANGGOTA KELOMPOK TANI DALAM PROGRAM UPAYA KHUSUS PADI JAGUNG KEDELAI (UPSUS PAJALE) DI KECAMATAN METRO BARAT KOTA METRO - Hafiza Ayu Rizqi; Sumaryo Gitosaputro; Serly Silviyanti (Lampung University, 2019)
The purpose of this research is to assess implementation of Upsus Pajale Program, participation of farmer group members, and analyse factors related to the participation of farmers group members in the Upsus Pajale Program. This is a survey which is purposively undertaken in West Metro Sub district, involving 52 farmer households. The study was carried out from September to October 2017. Data are analyzed using qualitative-descriptive analysis and Rank Spearman correlation test. The results show that factors related to participation of farmer group members were farmers frequency in attending agricultural extension meeting and level of motivation. However, farmer’s age, formal education level, and land ownership have no relation with participation. Overall, participation of farmer group members in Upsus Pajale Program in West Metro Sub district is quite active.Key words: participation of famer group members, Upsus Pajale